The Role of the Iron Transporter ABCB7 in Refractory Anemia with Ring Sideroblasts - Boultwood, Jacqueline (Public Library of Science, 2008)
Refractory Anemia with Ring Sideroblasts (RARS) is an acquired myelodysplastic syndrome (MDS) characterized by an excess iron accumulation in the mitochondria of erythroblasts. The pathogenesis of RARS and the cause of this unusual pattern of iron deposition remain unknown. We considered that the inherited X-linked sideroblastic anemia with ataxia (XLSA/A) might be informative for the acquired disorder, RARS. XLSA/A is caused by partial inactivating mutations of the ABCB7 ATP-binding cassette transporter gene, which functions to enable transport of iron from the mitochondria to the cytoplasm. Furthermore, ABCB7 gene silencing in HeLa cells causes an accumulation of iron in the mitochondria. We have studied the role of ABCB7 in RARS by DNA sequencing, methylation studies, and gene expression studies in primary CD34(+) cells and in cultured erythroblasts. The DNA sequence of the ABCB7 gene is normal in patients with RARS. We have investigated ABCB7 gene expression levels in the CD34(+) cells of 122 MDS cases, comprising 35 patients with refractory anemia (RA), 33 patients with RARS and 54 patients with RA with excess blasts (RAEB), and in the CD34(+) cells of 16 healthy controls. We found that the expression levels of ABCB7 are significantly lower in the RARS group. RARS is thus characterized by lower levels of ABCB7 gene expression in comparison to other MDS subtypes. Moreover, we find a strong relationship between increasing percentage of bone marrow ring sideroblasts and decreasing ABCB7 gene expression levels. Erythroblast cell cultures confirm the low levels of ABCB7 gene expression levels in RARS. These data provide an important link between inherited and acquired forms of sideroblastic anemia and indicate that ABCB7 is a strong candidate gene for RARS.